If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(3 + -4x) = 6 + 20x + -9 (3 * -5 + -4x * -5) = 6 + 20x + -9 (-15 + 20x) = 6 + 20x + -9 Reorder the terms: -15 + 20x = 6 + -9 + 20x Combine like terms: 6 + -9 = -3 -15 + 20x = -3 + 20x Add '-20x' to each side of the equation. -15 + 20x + -20x = -3 + 20x + -20x Combine like terms: 20x + -20x = 0 -15 + 0 = -3 + 20x + -20x -15 = -3 + 20x + -20x Combine like terms: 20x + -20x = 0 -15 = -3 + 0 -15 = -3 Solving -15 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 16p^2-36= | | 5x+11=83-3x | | 3p+4q=52 | | x^2-8X-32=0 | | 2+3b=-4 | | 4(x+2)+10=6x-(x+9) | | -4(x+4)-3=-19 | | 5-8n=10 | | 4[7x-5(y-3)]= | | 6+4x=18+x | | 3c-6=5c+9 | | 5(x+2)-(x-2)=0 | | 8+1= | | 14-5n(3)=n | | 8x-14=2x+4 | | 6=2-4x | | 45-5x=4x+17 | | 11x-23=109 | | 8-8x=152-36x | | 3y-y+2y-5=7-y+5 | | 2(5m+4)-3(m-4)= | | 6x+8y=27 | | 8-8x=152-36 | | 9a+2=4a-18 | | 4g-12=8 | | 3+9= | | 2(x+7)=6x+9-4 | | 10n-30=40 | | -126-7x=152-36x | | (n-10)*10=70 | | 3+81= | | 5=-9x+23 |